The construction of knowledge and teaching practices about collective health in Social Work - Bru, Gabriela Silvina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
Health is an area of ​​extensive development and professional practice of social work. The article aims to reflect on the production of knowledge in the field of collective health from social work. The interest in this topic arises from teaching practice in the Collective Health subject of the Social Work career at the UNMDP (Argentina). To carry out this exercise we reviewed bibliographic sources and identified some of the topics investigated from social work in the field of collective health. The main section of the article is structured in three stages. The first exposes the theoretical framework from which we think about collective health as a field of study. The second consists of a description of publications on health and social work. Finally, the third is dedicated to rethinking how collective health training in the social work degree program contributes to the construction of disciplinary knowledge. The conclusions state that the incorporation of issues related to collective health into the social work curriculum is key in the construction of analytical schemes to think about research problems and, thus, to fertilize the investigative attitude of the profession.